IMPLEMENTASI TOTAL QUALITY MANAGEMENT TERHADAP KUALITAS PRODUK PADA PT. TRI MUSTIKA COCOMINAESA AMURANG - Kading, Meylani Selvi; Pangemanan, Sifrid S.; Gerungai, Natalia Y. T. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The influence of globalization in the industrial world today has caused competition between companies to become increasingly strict and competitive. The company's success is seen from the quality of products produced by the company. Total Quality Management is an ongoing process to achieve a better level of quality in meeting customer needs. The purpose of this research is to find out how the implementation of Total Quality Management at PT. Tri Mustika Cocominaesa Amurang. The method used is descriptive analysis. PT. Tri Mustika Cocominaesa applies ethics, integrity, trust, training, teamwork, leadership, appreciation, and communication to be successful in implementing Total Quality Management.Keywords: Total Quality Management TQM, Product Quality.